2019
DOI: 10.4314/ijbcs.v13i3.32
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the powdery formulation of <i>Hyptis spicigera</i> (Lamiaceae), <i>Azadirachta indica</i> (Meliaceae) and <i>Vepris heterophylla</i> (Rutaceae) Single and in combination on <i>Tribolium castaneum</i> Herbst. (Coleoptera: Tenebrionidae)

Abstract: The red flour weevil, Tribolium castaneum (Herbst 1797) is a pervasive pest, polyphagous which is becoming increasingly resistant to the normal insecticides. Finding alternative insecticides to those because of their inefficiency pollute the environment and poison consumers is an emergency. An ethno-botanical survey conducted with about 300 farmers in the Far North region of Cameroon identified 15 local plants insecticides associated with food during storage in combination with two or three others. Among these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…quinquefasciatus [20]. The mixture of plants extract does not necessarily give an additive effect and this hypothesis is supported by Ayiki et al, [22] and those of Ngatanko and Ngamo [23]. The differences between the insecticidal activities of the extracts individually and in binary combinations might be due to the composition and chemical nature of the active compounds acting jointly or independently on mosquitoes.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…quinquefasciatus [20]. The mixture of plants extract does not necessarily give an additive effect and this hypothesis is supported by Ayiki et al, [22] and those of Ngatanko and Ngamo [23]. The differences between the insecticidal activities of the extracts individually and in binary combinations might be due to the composition and chemical nature of the active compounds acting jointly or independently on mosquitoes.…”
Section: Discussionmentioning
confidence: 77%
“…The binary combination 50%Ca + 50%Lc induced a synergistic action on Anopheles gambiae larvae 24 hours postexposure and was found to be the best combination because it optimized the efficacy of the combination by considerably lowering the LC 50 value. The efficacy of plant extract mixtures would depend on the type of mixture produced (proportional or balanced) and the species considered [22]. Previous works revealed that several varieties of Citrus contained ingredients that can be used as a natural insecticide in mosquitoes [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best combination was the synergistic combination 25%Ca+75%Hs, followed by the additive combinations 75%Ca+25%Hs and 50%Ca+50%Hs. The efficacy of plant extract mixtures depends on the type of mixture produced (proportional or balanced) and the species considered 18 52 . The adulticidal effects of diallyldisulfide, eugenol, methyl eugenol, limonene, carvone, α-pinene, eucalyptol, eudesmol and their combinations have been reported previously against Aedes aegypti 53 .…”
Section: Discussionmentioning
confidence: 99%
“…For example in the western highlands of Cameroon plant materials consisting of leaves, seed and/or roots; Cupressus arizonica, Eucalyptus grandis, Ocimum gratissimum, Vetiveria zizanioides, Balanites aegyptiaca, Lophira lanceolata, Hemizygia welwitschii, Plectranthus glandulosus, Laggera pterodonta and Azadirachta indica are considered as alternatives to synthetic insecticides for the protection of stored maize grains against Sitophilus zeamais [43,[45][46][47] Dried ground leaves/seed powders of some spices (Syzygium aromaticum, Piper guineense, Aframomum citratum and Ocimum basilicum), leave/seed powder of Hemizygia welwitschii and/or Plectranthus glandulosus, Azadirachta indica have an insecticidal potential against the cowpea weevil (Callosobruchus maculatus), common bean weevil and maize, thus small-scale farmers have been using them to protect their stored-product [45,46,48,49]. In the Far North region of Cameroon, powders of Hyptis spicigera (Lamiaceae), A. indica (Meliaceae) and Vepris heterophylla (Rutaceae) are mostly used as insecticides single or associated with food during storage in combination with two or three others plants to control the red flour weevil (Tribolium castaneum) [50]. The flours from Phaseolus sativum and Phaseolus vulgaris seeds are also used to protect sorghum grains against the attack of Sitophilus oryzae [51].…”
Section: Powder Formulationmentioning
confidence: 99%